PENGARUH CURRENT RATIO (CR) DAN DEBT TO EQUITY RATIO (DER) TERHADAP RETURN ON ASSET RATIO (ROA) PADA PT ADHI KARYA TBK PERIODE 2014-2023 - Nurhidayah, Indania; Daeng Matta, Yusran (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of Current Ratio (CR) and Debt to Equity Ratio (DER) on Return on Asset Ratio (ROA) in PT Adhi Karya Tbk for the 2014-2023 period. The method in this study is quantitative descriptive. The data analysis methods used include: Classical Assumption Test (Normality Test, Multicollinearity Test, Heteroscedasticity Test, and Autocorrelation Test), Determination Coefficient Test, Multiple Linear Regression Test, Hypothesis Test (t Test (Partial) and F Test (Simultaneous)). The results of this study show that the Current Ratio (CR) partially has an effect and significantly on the Return on Asset Ratio (ROA) because t is calculated 3.560 > t table 2.364 and the sig value is 0.009 < 0.05. Debt to Equity Ratio (DER) partially has no effect and is significant on the Return on Asset Ratio (ROA) because t is calculated 0.523 < t table 2.364, and with a significance level of 0.617 > 0.05. Simultaneously, the Current Ratio (CR) and Debt to Equity Ratio (DER) have an effect and significance on the Return on Asset Ratio (ROA) at PT Adhi Karya because F calculates 9.666 > F table 4.74, with a significance level of 0.010 < 0.05.